2008
DOI: 10.1111/j.1365-2036.2008.03639.x
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of hepatic functional impairment in compensated chronic hepatitis C: results from the Hepatitis C Anti‐viral Long‐term Treatment against Cirrhosis Trial1

Abstract: SUMMARY BackgroundThe spectrum of functional impairment in patients with compensated chronic hepatitis C is incompletely defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…In the HALT-C cohort we found that the dual cholate test outperformed standard lab tests, Ishak fibrosis score, and other QLFTs in prediction of outcomes 14,24,26 . Subsequently, we compared the performance of DSI against Ishak fibrosis score, platelet count, and MELD score first by examination of respective ROC curves.…”
Section: Clinical Applicationsmentioning
confidence: 85%
See 4 more Smart Citations
“…In the HALT-C cohort we found that the dual cholate test outperformed standard lab tests, Ishak fibrosis score, and other QLFTs in prediction of outcomes 14,24,26 . Subsequently, we compared the performance of DSI against Ishak fibrosis score, platelet count, and MELD score first by examination of respective ROC curves.…”
Section: Clinical Applicationsmentioning
confidence: 85%
“…The dual cholate test outperformed a battery of metabolic tests in predicting cirrhosis 14,24,26 , and DSI>19 predicted cirrhosis and risk for future clinical outcomes 27,28 . D4-cholate concentration >1μM at 60 minutes after oral dosing, is equivalent to DSI >19 27,28 .…”
Section: Clinical Applicationsmentioning
confidence: 95%
See 3 more Smart Citations